A new classification and treatment protocol for mandibular condylar fractures - Rikhotso, Risimati Ephraim (My University, 2019)
Introduction Despite decades of study, a consensus on therapeutic approaches to condylar fractures remains elusive, and the vexing question of invasive (open reduction or surgical treatment) or non-invasive (closed treatment or non-surgical treatment) therapy remains to be definitively answered. This lack of a standardised treatment protocol for condylar fractures often results in the haphazard and often subjective application of treatment schedules. This study aimed to present a new classification system for mandibular condylar fractures. Furthermore, this randomised, clinical single-centre study compared the outcomes of mandibular condylar fractures treated by closed treatment with those treated by open reduction with rigid internal fixation. Factors which influence treatment outcomes of mandibular condylar fractures were also evaluated, and used to design a mandibular condyle scoring system and management protocol. Materials and methods Patients older than 18 years withWits Types II, III and IV mandibular condylar fractures were prospectively randomised into the open and closed treatment groups. In the open reduction and internal fixation (ORIF) group fractures were approached via a retromandibular incision. In the closed treatment (CT) group patients were placed in intermaxillary fixation (IMF) for 1 week. In both groups, elastic guidance was used for 5 weeks and physiotherapy for 3 months. Both groups were assessed for parameters vi such as mouth opening, occlusion, range of movement, TMJ function and complications at 1 and 6 weeks, 3, 6 and 12 months. Results A total of 116 patients with MCFs were included in the study. Of these, only 10 (9%) were female. There was a total of 132 fractures (100 unilateral, 16 bilateral). Of the 100 unilateral fractures 41 occurred on the left side and 59 on the right. The most common type of fracture was Type IIB (89.7%) followed by Type III (7.4%) and Type IV (2.9%). The aetiology of the fracture was alleged assault in 76 patients (65.5%), road traffic accident in 17 (14.6%) and falls in 16 (13.7%). Symphyseal and parasymphyseal fractures were the most commonly associated fractures (n=75) followed by body (n=21) and angle fractures (n=7). Only 15 (13%) patients had isolated mandibular condylar fractures (MCFs). Sixty eight (59%) patients were treated by CT and 48 (41%) patients were treated by ORIF. After a follow-up of 12 months, no significant differences were observed between the two groups for mouth opening, protrusion, pain, TMJ function and laterotrusive movements to the non-fractured side. Laterotrusive movements towards the fractured side in unilateral cases were, however, better in the closed group than in the open group (p=0.038). In the closed group, 14 (21%) patients had malocclusion and 18 (27%) patients had deviations greater than 2 mm. In the open group, 9 patients had transient facial nerve palsies which resolved within 3 months, 2 patients had hypertrophic scars, 3 had keloids, 4 had parotid fistulae which resolved within 6-8 weeks, 1 had malocclusion, and 3 had deviations.
A thesis submitted to the Faculty of Oral Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy,2019
Keywords: Mandibular Condyle--injuries; Mandible; Fracture Fixation, Internal--methods